การสร้างฐานอำนาจทางการเมืองของกลุ่มการเมือง ในการเมืองท้องถิ่น : ศึกษาเฉพาะกรณีกลุ่ม "สันติธรรม" ในเทศบาลเมืองนครปฐม - เดชะ สิทธิสุทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
This research is aimed at studying the process of building up political power base at local government politics as well as a political group as a political party. The method used in this study is composed of official documents, laws, rules and regulations concerned. In addition, interviews and observation are made in order to get informations needed. The findings show that the people who played role in The political power base building is The political group leader. By mean of the leader group gains support by a personal relations and interest exchanging with the group members and supporters with a view to win election in local election. After election, the supporters will receive benefits from their partions in various ways, especially public projects.